2005
DOI: 10.1016/j.clpt.2005.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Variation in oral clearance of saquinavir is predicted by CYP3A5*1 genotype but not by enterocyte content of cytochrome P450 3A5

Abstract: The CYP3A5*1 genotype is associated with increased saquinavir CL/F. This does not appear to reflect intestinal CYP3A5 expression and presumably reflects the contribution of hepatic CYP3A5. The interaction with Seville orange juice in subjects not expressing CYP3A5 supports a role for intestinal CYP3A4. However, the modest nature of the interaction, combined with the inability to detect a correlation between CL/F and CYP3A4 enterocyte content, supports our recent in vitro work suggesting a smaller contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
71
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 43 publications
(117 reference statements)
1
71
2
Order By: Relevance
“…clearance and lower steadystate blood concentrations and require higher tacrolimus doses to achieve therapeutic blood concentrations than patients lacking the CYP3A5*1 allele (Bader et al, 2000;Hesselink et al, 2003Hesselink et al, , 2004Thervet et al, 2003;Haufroid et al, 2004). Recent studies evaluating saquinavir, indinavir, and quinidine have found a positive correlation between the presence of a CYP3A5*1 allele and higher oral clearance (Fröhlich et al, 2004;Mouly et al, 2005;Anderson et al, 2006;Mirghani et al, 2006). Similar to previous observations (Floyd et al, 2003;Yu et al, 2004), the CYP3A5*1 allele was not associated with differences in the ability of rifampin to induce ERBT values in our African American cohort.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…clearance and lower steadystate blood concentrations and require higher tacrolimus doses to achieve therapeutic blood concentrations than patients lacking the CYP3A5*1 allele (Bader et al, 2000;Hesselink et al, 2003Hesselink et al, , 2004Thervet et al, 2003;Haufroid et al, 2004). Recent studies evaluating saquinavir, indinavir, and quinidine have found a positive correlation between the presence of a CYP3A5*1 allele and higher oral clearance (Fröhlich et al, 2004;Mouly et al, 2005;Anderson et al, 2006;Mirghani et al, 2006). Similar to previous observations (Floyd et al, 2003;Yu et al, 2004), the CYP3A5*1 allele was not associated with differences in the ability of rifampin to induce ERBT values in our African American cohort.…”
Section: Discussionsupporting
confidence: 74%
“…Several recent reports suggest the CYP3A5*1 allele may impart important clinical consequences because of the higher clearance of some CYP3A drugs (Mouly et al, 2005;Jin et al, 2007;Josephson et al, 2007;Isoherranen et al, 2008). More recently, low hepatic CYP3A activity was found to be associated with the risk for corticosteroid-induced osteonecrosis (Kaneshiro et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19) Some clinical studies have demonstrated that CYP3A5 is of minimal importance in terms of the overall CYP3A metabolic phenotype for some CYP3A substrates, such as midazolam, [85][86][87][88] alfentanil, 88) and saquinavir. 89) However, the present information suggests the following: the relative contribution of polymorphic CYP3A5 to the metabolism of CYP3A4/5 substrates, especially in hydroxylation reactions, is significant, and the risk of adverse drug-drug interactions due to competitive and/or mechanism-based inhibition mediated by CYP3A5 is lower than that mediated by CYP3A4, although the limitations of this study should be considered when interpreting the results. The causal factor(s) and reasons for the different findings for the kinetic parameters and inhibi-tion constants should be determined in future drug metabolism and drug interaction studies.…”
Section: Discussionmentioning
confidence: 44%